Qualitative phytochemical analysis and antimicrobial activity of Piper sarmentosum leaves extract against selected pathogens - Hartini Yusof,; Nur Aziatul Syakila Mohamad Radzi,; Reena Leeba Richard, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The controversial usage of antiseptic in treating wound infections had become a huge issue over the years due to its minimal effectiveness and high toxicity level that are harmful to humans. Hence, numerous studies had been carried out to determine other possible approaches including herbal remedies. The alarming situation had led us to study on Piper sarmentosum and its antimicrobial activity against selected pathogens. In present study, methanol extract of Piper sarmentosum leaves were prepared to investigate the presence of phytochemical compounds. The in vitro antimicrobial activity of crude methanolic extract was evaluated using disc diffusion and microdilution broth methods. The study demonstrated the antimicrobial activity of leaves extract against Staphylococcus aureus (7 mm) and Escherichia coli (6.5 mm). However, no zone of inhibition was observed against Pseudomonas aeruginosa. Meanwhile, the MIC values for Staphylococcus aureus was 6.25 mg/mL whilst Escherichia coli was 12.5 mg/mL. In addition, the phytochemical screening results revealed that the extract contained glycosides, flavonoids, terpenoids, alkaloids and phenolics. In conclusion, methanolic extract of Piper sarmentosum leaves has the potential as a new, effective alternative towards current drugs that are available for skin-associated infection. The findings from this study are crucial in providing latest information of the plant’s additional values that can be incorporated as a baseline for current and future studies as well as in investigating other possible plants that are beneficial for health purposes, particularly for combating skin-associated infection.